Physical activity participation and the association with work‐related upper quadrant disorders (WRUQDs): A systematic review. (29th June 2017) - Mansfield, Michael; Thacker, Michael; Smith, Toby
Abstract: Background: Workers in various occupations often report work‐related upper quadrant disorders (WRUQDs). Research has shown that associative factors for WRUQDs include psychosocial and environmental elements, gender and physical activity levels. To date, no review has investigated whether physical activity participation is associated with and/or predicts the development of WRUQDs, so the present study set out to determine this. Methods: A systematic review was conducted including searches of PubMed (MEDLINE), EMBASE and CINAHL from inception to 31 March 2017. Quantitative studies, including any outcome measure of physical activity participation and its association with and/or prediction of WRUQDs, were included. One reviewer conducted the search and two reviewers independently assessed eligibility and completed methodological quality assessment using a modified Downs and Black checklist. Data were analysed narratively. Results: Eight studies were eligible for inclusion in the final review. The quality of these ranged from moderate to high quality. Three studies reported no statistical difference between physical activity participation and the risk of developing WRUQD. Three studies reported a negative and one study a positive association between physical activity participation and WRUQDs. One study reported that little or no physical exercise participation was a risk factor for WRUQD. Conclusions: There is limited evidence for a negative association between physical activity participation and the development of WRUQDs. However, this was not a consistent finding across all studies included. Further research is indicated in standardizing diagnostic criteria and the measurement of physical activity participation in this patient population.